The electrical and optical properties of TiO2 reinforced by carbon nanotubes - Guler, Seval Hale; Guler, Omer (Pamukkale Univ, 2017)
In this study, Carbon Nanotubes (CNT) synthesized with Chemical Vapour Deposition (CVD) were reinforced with 0.1, 0.2, 1 and 2% weight in Titanium dioxide (TiO2). Structural characterization of samples was analyzed by Scanning Electron Microscope (SEM). Electrical conductivities of samples, based on temperature, were surveyed. Optical properties were determined using UV-VIS spectrometer. Increase in CNT rate in composites caused electrical conductivity both room and rising temperature. Furthermore, CNT caused the increases in ability of TiO2's to absorb UV beam, and the reduces on forbidden energy gap (Eg).
Keywords: Titanium dioxide; Carbon nanotube; Optical properties